Organoleptic quality assessment of Theobroma cacao L. in cocoa farms in northern Huila, Colombia (2018)
Cocoa is a food product with sensory and organoleptic attributes that depends on postharvest processes such as fermentation. This process affects not only the sensory profile, but also chemical reactions and therefore, the quality of the product. Hence, the aim of this study is to carry out a chemical and sensory characterization of cocoa (Theobroma cacao L.) samples from different cocoa farms in the department of Huila, Colombia. Moreover, a bromatological analysis was performed, secondary metabolites (caffeine and theobromine) and total polyphenols were determined, as well as volatile fraction compounds using gas chromatography by solid phase microextraction in the headspace mode (HS-SPME); finally, the samples were classified (acceptable, unpleasant and contaminated) according to a tasting panel. In general, bromatological characteristics of cocoa samples showed acceptable levels, presence of special volatile compounds (linalool and linalool oxide) that affected sensory attributes (floral). Likewise, levels of caffeine and theobromine had adequate levels that resulted in bitter taste. A relationship was found between volatile fraction compounds and bromatological analysis variables, secondary metabolites and total polyphenols that affected the quality of the product.